Discretionary behavior and performance in educational organizations the missing link in educational leadership and management - Duyer, Ibrahim; Normore, Anthony H. (Bingley, U.K. : Emerald, 2012)
The purpose of this volume is to contribute for the development of a parsimonious and coherent theory/understanding in discretionary behavior in organizations, educational organizations in particular. The volume will set a stage for the discussion of significance and timeliness of discretionary behavior towards solving long lasting issues in educational organizations. The volume also will create an environment where the future discourse and direction of discretionary behavior in educational organizations are discussed.
ch. 1. The relationship between the four branch model of emotional intelligence and discretionary behavior of university educators / David L. Turnipseed, Elizabeth VandeWaa -- ch. 2. Teachers' organizational citizenship behavior : an empirical examination of the subjective and dynamic nature of the boundary between in-role and extra-role behavior / Elena Belogolovsky, Anit Somech -- ch. 3. Organizational citizenship behaviors of teachers : antecedents, transformational leadership, and contradictions / Nancy L. Ras -- ch. 4. Performance beyond expectations / Ibrahim Duyar, Anthony H. Normore -- ch. 5. Relationship between demographic variables and organizational citizenship behavior among community college lecturers / Noriah Abdul Malek, Fatt Hee Tie -- ch. 6. Nature of leadership discretions and sustainability of education innovations : critical connections / Tamara Savelyeva, Yeung Lee -- ch. 7. Coalface academic leadership in Australian higher education : discretionary behaviour through empowerment / Judy Nagy -- ch. 8. What we do here is who we are / Nancy L. Ras -- ch. 9. The relationship between organizational justice, organizational trust and organizational citizenship behaviors in secondary schools in Turkey / Kursad Yilmaz, Yahya Altinkurt -- ch. 10. Teachers supervising teaching assistants : assigned role or discretionary behaviour? : reflections from the United Kingdom / Jill Morgan, Betty Y. Ashbaker -- ch. 11. The possible consequences of organizational citizenship behaviors in drug and alcohol prevention education : some insights from Israeli teachers and principals / Izhar Oplatka -- ch. 12. What do we know about assistant principals? : a cross-national examination of the factors affecting task performance, discretionary performance, and future career aspirations of assistant principals / Ibrahim Duyar, Inayet Aydin.
Includes index.
Print version record
Keywords: Education -- Leadership; Education -- Administration -- General; Education -- Organizations & Institutions; Organization & management of education; Philosophy & theory of education; School management and organization